2017
DOI: 10.1038/aps.2017.167
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Ivabradine treatment on serum levels of cardiac biomarkers sST2, GDF-15, suPAR and H-FABP in patients with chronic heart failure

Abstract: Chronic heart failure (CHF) represents a major cause of hospitalization and death. Recent evidence shows that novel biomarkers such as soluble suppression of tumorigenicity (sST2), growth-differentiation factor-15 (GDF-15), soluble urokinase plasminogen activator receptor (suPAR) and heart-type fatty acid binding protein (H-FABP) are correlated with inflammatory and ischemic responses in CHF patients. In this study we examined the effects of Ivabradine that inhibited the hyperpolarization-activated cyclic nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 41 publications
0
24
0
1
Order By: Relevance
“…In a small study, sST2 was significantly higher in patients with DCM than in controls 197 . sST2 has been found to predict the risk of developing heart failure in patients with DCM in several recent studies 193,[198][199][200] . When combined with NT-proBNP, which is released under conditions of pressure overload and, therefore, is a marker for heart failure, serum sST2 levels provide additive value in predicting sudden death in patients with heart failure and an LVEF ≤45% 201 .…”
Section: Serum Biomarkersmentioning
confidence: 99%
“…In a small study, sST2 was significantly higher in patients with DCM than in controls 197 . sST2 has been found to predict the risk of developing heart failure in patients with DCM in several recent studies 193,[198][199][200] . When combined with NT-proBNP, which is released under conditions of pressure overload and, therefore, is a marker for heart failure, serum sST2 levels provide additive value in predicting sudden death in patients with heart failure and an LVEF ≤45% 201 .…”
Section: Serum Biomarkersmentioning
confidence: 99%
“…In the last years, novel cardiac biomarkers have emerged as promising diagnostic tools for the assessment of different cardiovascular disease entities [10,11]. As a result to the complex pathophysiological background of most cardiovascular diseases, a multi-marker approach was reported as most effective for diagnosis, therapy monitoring and risk prediction due to the incorporation of different pathophysiologic processes covered by each respective marker [10,12].…”
Section: Introductionmentioning
confidence: 99%
“…The novel biomarkers sST2, GDF-15, soluble urokinase-type plasminogen activator receptor (suPAR), and H-FABP showed a response in patients with chronic heart failure. 17 In patients with acute myocardial infarction, the biomarkers (sST2, GDF-15, H-FABP, and suPAR) were significantly elevated than in the control groups without coronary heart disease. 14…”
Section: Cardiovascular Biomarkersmentioning
confidence: 88%
“…13 Recent studies showed significantly elevated biomarkers (sST2, GDF-15, and H-FABP) in patients with acute myocardial infarction or heart failure than in patients without coronary artery disease and good systolic left ventricular function. [13][14][15] An association of these biomarkers and cardiac diseases was recently found, but additional clinical trials are warranted to investigate the clinical significance of these findings. In our patient, we wanted to investigate the concentrations of the biomarkers mentioned earlier, because they portray various pathophysiological pathways of the heart.…”
Section: Cardiovascular Biomarkersmentioning
confidence: 99%